The Role, Strategies, and Innovations of School Principals as Change Leaders in the Implementation of the Independent Curriculum - Nari, Nola; Khaidir, Christina; Arif, Yudabbirul; Gistituati, Nurhizrah; Rusdinal, Rusdinal (Postgraduate School, Universitas Negeri Padang, 2024)
This study investigates the role of school principals as change leaders in implementing the Independent Curriculum in Indonesia. It explores their strategies, innovative practices, and the factors contributing to both the successes and challenges of curriculum application. Adopting a qualitative methodology, data were gathered through purposive sampling, with school principals serving as primary informants. The findings reveal that principals are instrumental in driving curriculum reform by engaging in academic supervision, cultivating collaborative school environments, and promoting student-centered learning approaches. Key strategies identified include organizing professional development initiatives, fostering stakeholder partnerships, and efficiently managing resources to align teaching methodologies with the curriculum’s objectives. Innovative practices, such as establishing professional learning communities and introducing project-based learning activities, further facilitate the curriculum's adoption. The study identifies several factors that support the implementation of the Independent Curriculum, including active teacher involvement, government-sponsored training programs, and curriculum designs tailored to local contexts. The study highlights the critical need for continuous professional development, comprehensive strategic planning, and consistent policy support to overcome these obstacles. Effective leadership by school principals is essential for fostering a positive school culture and encouraging collaboration among stakeholders, thereby enabling systemic transformation.